Comparative Analysis of Financial Management Models in Developed and Developing Countries - Atik Andhayani; Agus Zainul Arifin; Baihaqi Baihaqi; Jamaluddin Majid; Fahrudin Fahrudin (Yayasan Adra Karima Hubbi, 2024)
Given the fundamental differences in economic structure, fiscal policy, and financial regulation between developed and developing countries, research on financial management models in both countries is very important. The aim of this research is to study and compare financial management models in developed and developing countries. Specific objectives include determining the main components of financial management models used in developed and developing countries, evaluating the factors that influence financial management performance in both groups of countries, evaluating how these different models impact economic stability and economic growth, and providing appropriate policy recommendations. can be applied to improve state financial management. This research uses both qualitative and quantitative approaches. Qualitative data was obtained through in-depth literature research on the theory and practice of financial management in developed and developing countries, and quantitative data was obtained through secondary data analysis from reports of international financial institutions, state financial reports and economic statistics. The effectiveness of financial management is strongly influenced by variables such as political stability, level of corruption, and institutional capacity. Developing countries face problems in terms of market credibility and trust, while developed countries have strong regulatory frameworks and easier access to international financial markets. This study finds that financial management models in developed and developing countries differ significantly, and that various economic, political and institutional components influence these differences. Countries that have better financial structures and more consistent policies tend to be better at managing their finances.